Preventing depression among older people living in rural areas: A randomised controlled trial of behavioural activation in collaborative care. (31st October 2020) - Almeida, Osvaldo P.; Patel, Hema; Kelly, Rachael; Ford, Andrew; Flicker, Leon; Robinson, Suzanne; Araya, Ricardo; Gilbody, Simon; Thompson, Sandra
Abstract: Objectives: This study aimed to test if a behavioural activation (BA) programme was more effective than usual care at reducing the risk of conversion to major depression over 52 weeks among adults aged 65 years or older living in rural Western Australia. Secondary aims were to test if participants assigned to the BA intervention experienced greater decline in the severity of depressive and anxiety symptoms than older adults treated with usual care over 26 and 52 weeks, as well as greater improvement in physical and mental health‐related quality of life. Methods: Randomised controlled clinical trial that started recruitment in February 2016 in rural Western Australia. We used the electoral roll to invite adults aged 65 years or over living in suitable regions of Western Australia to take part in the study. We recruited those who consented and screened positive to at least one of the two Whooley questions: feeling down/depressed/hopeless or little interest or pleasure over the past month. Participants were randomly assigned to usual care or usual care plus a phone‐delivered BA program (1:1). The intervention consisted of a self‐managed BA program supported by three 45‐min phone sessions delivered by a BA therapist over a period of 8 weeks. We used the DSM‐5 criteria to establish the presence of a major depressive episode, and Patient Health Questionnaire, Generalised Anxiety Disorder Scale and SF‐36 to assess symptoms of depression, anxiety and quality of life. Results: Of the 309 older adults randomised, 307 started the trial: 153 usual care and 154 BA (computer‐generated random permuted even blocks ranging in size from 8 to 20). Six participants developed a major depressive episode during follow‐up, four of them in the usual care group (odds ratio of depression associated with the intervention = 0.49, 95% CI = 0.04, 3.49—blind assessment). Seventy‐three (23.8%) participants were lost over 52 weeks—there were no differences between usual care and intervention group. Intention‐to‐treat analyses using mixed regression models found modest non‐significant effects of the BA intervention, while complete‐case analyses showed that participants treated with BA compared with usual care experienced significant improvements in depression and anxiety symptoms over 52 weeks, as well as improved mental health quality of life. Conclusions: Few participants developed a major depressive episode during follow‐up. The BA intervention was associated with improved symptoms of depression and anxiety, although the clinical significance of these benefits remains unclear.